Clinical diagnoses and outcomes of 4619 hospitalised cases of laboratory-confirmed invasive meningococcal disease in England: Linkage analysis of multiple national databases. Issue 5 (November 2016) - Edge, Chantal; Waight, Pauline; Ribeiro, Sonia; Borrow, Ray; Ramsay, Mary; Ladhani, Shamez
Summary: Background: Invasive meningococcal disease (IMD) is rare but remains one of the most feared infectious diseases worldwide. We linked multiple national datasets to describe disease characteristics and outcomes of IMD in England over a five-year period. Methods: IMD cases confirmed by Public Health England (2007–11) were linked with national hospitalisation records and death registrations. Cases were analysed by age, gender, capsular group, clinical presentation, diagnostic test and outcome. Risk factors for death were assessed using multivariable logistic regression. Results: Overall, 4619 of 5115 (90.30%) laboratory-confirmed IMD cases were successfully linked to a hospitalisation record. Group B meningococci were responsible for 87.33% (n = 4034) of hospitalised IMD cases, ranging from 93.56% (2294/2452) in <15 year-old to 53.52% (152/284) among ≥65 year-old. Most cases presented with meningitis only (n = 2057, 44.53%), septicaemia only (n = 1725, 37.35%) or both meningitis and septicaemia (n = 389, 8.42%). Over half the cases (2526/4619, 54.69%) were confirmed by PCR only, 22.91% (1058/4619) by culture only and 22.41% (1035/4619) by both. The case fatality rate was 4.46% (206/4619; 95% CI, 3.88–5.10%) and varied by age, clinical presentation and capsular group. Children under 15 years who died within 30 days of diagnosis were significantly more likely to have been diagnosed by culture than by PCR alone (OR, 1.56; 95% CI, 1.02–2.39; P = 0.040). Conclusions: We identified complex interactions between age, meningococcal capsular group, clinical presentation, diagnostic method and death. The recent introduction of two new meningococcal immunisation programmes in the UK should significantly reduce IMD cases and deaths in the coming years.